Influence of oxygen pressure on the ferroelectric properties of epitaxial BiFeO3 thin films by pulsed laser deposition - Yao, Kui (2011)
The growth window of multiferroic BiFeO3 thin films is very small. Both temperature and oxygen pressure will affect the film quality and phase purity significantly. We demonstrate here that even within the window where phase pure BiFeO3 thin films can be obtained, different oxygen partial pressures still lead to substantial variation in Bi/Fe ratio in the film, which closely link with the corresponding ferroelectric properties. Piezoelectric force microscopy also reveals significant difference in the domain structures of these films. A defectdipole complex model is proposed to explain the difference in the electrical properties and domain structures for films grown under different oxygen pressures.